2015
DOI: 10.3846/16484142.2015.1046137
|View full text |Cite
|
Sign up to set email alerts
|

Macroscopic Modeling and Control of Emission in Urban Road Traffic Networks

Abstract: Abstract. This work suggests a framework for modeling the traffic emissions in urban road traffic networks that are described by the Network Fundamental Diagram (NFD) concept. Traffic emission is formalized in finite spatiotemporal windows as a function of aggregated traffic variables, i.e. Total Travel Distances (TTDs) in the network and network average speed. The framework is extended for the size of an urban network during a signal cycle -the size of a window in which the network aggregated parameters are m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 18 publications
0
9
0
1
Order By: Relevance
“…where l i is the length of link i, n is the number of links (Williams et al 1987;Csikós, Tettamanti, and Varga 2015). The second approach interprets the MFD of one single road link of the network, i.e.…”
Section: Macroscopic Model For Urban Trafficmentioning
confidence: 99%
See 1 more Smart Citation
“…where l i is the length of link i, n is the number of links (Williams et al 1987;Csikós, Tettamanti, and Varga 2015). The second approach interprets the MFD of one single road link of the network, i.e.…”
Section: Macroscopic Model For Urban Trafficmentioning
confidence: 99%
“…The idea of urban MFD has been generally researched in the previous decades, e.g. Mahmassani, Williams, and Herman (1987), Daganzo (2007), Keyvan-Ekbatani, Papageorgiou, and Papamichail (2014), Csikós, Tettamanti, and Varga (2015), He, He, and Guan (2014), Geroliminis and Daganzo (2008). Furthermore, Guan and Shuyan (2008) found that the three-phase traffic theory and fundamental diagram are not conflicting when it comes to the urban area.…”
Section: Introductionmentioning
confidence: 99%
“…ahol l i az i-edik hálózati útszakasz hossza, n pedig az útszakaszok száma [5], [6]. A kifejlesztett szoftveres környezet célja az is, hogy a most kiépülő zalaegerszegi autonóm tesztpályán [14] közvetlenül alkalmazható legyen.…”
Section: Bevezetőunclassified
“…The importance of relevant average speed forecast is straightforward for ITS applications, e.g. (Csikós et al 2015a;Ficzere et al 2014). At the same time, it must be emphasised that resources' sharing based services also require information sharing.…”
Section: Introductionmentioning
confidence: 99%